2021
DOI: 10.1007/978-3-030-85616-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Sniff Before You Act: Exploration of Scent-Feature Associations for Designing Future Interactions

Abstract: It has long been known that our sense of smell is a powerful one that affects emotions and behaviors. Recently, interest in the sense of smell has been growing exponentially in HCI. However, the potential of smell to inspire design is still underexplored. In this paper, we first investigated crossmodal correspondences between scents and selected features relevant for design (clustered in sensory, bodily, and qualitative features). Then, we created a set of cards (EssCards) to visually summarize the key finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…For example, the lemon pattern was paired with a fresh smell, and the image of a rose was paired with a floral smell. The packaging design with the picture of a rose also contained a very soft texture which was found to be related to flower connotations in previous studies (Brianza et al, 2021).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, the lemon pattern was paired with a fresh smell, and the image of a rose was paired with a floral smell. The packaging design with the picture of a rose also contained a very soft texture which was found to be related to flower connotations in previous studies (Brianza et al, 2021).…”
Section: Discussionmentioning
confidence: 62%
“…Past research demonstrated that certain visual symbols can be paired with specific odors (Martino & Marks, 2000). According to Brianza et al (2021), lemon odor is associated with rough textures, while rose odor is associated with soft textures and rounded shapes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lemon pattern was paired with a fresh smell, and the image of a rose was paired with a floral smell. The packaging design with the picture of a rose also contained a very soft texture which was found to be related to flower connotations in previous studies (Brianza et al, 2021). On the other hand, when the packaging presented odor-neutral objects (such as the human body or abstract shapes), the participants' responses were not uniform.…”
Section: Odor Associationsmentioning
confidence: 78%
“…Past research demonstrated that certain visual symbols can be paired with specific odors (Martino & Marks, 2000). According to Brianza et al (2021), lemon odor is associated with rough textures, while rose odor is associated with soft textures and rounded shapes. Rounded forms can also be connected with vanilla smell or raspberry.…”
mentioning
confidence: 99%